Harnessing Floodwater of Hill Torrents for Improved Spate Irrigation System Using Geo-Informatics Approach - Wan Faizal, Wan Ishak; Saher, Faisal Nadeem; Nasly, Mohamed Ali; Tuty Asmawaty, Abdul Kadir; Yahaya, Nasehir Khan E. M. (International Science Congress Association, 2014)
In semi-arid regions, sustainability of agricultural system is most demanding in view of economical approaches for agricultural water management and its ensured availability. Flood flows of hill torrents have potential prospects for development to meet growing demands of water for agriculture. However to harvest this potential through traditional systems is not a success story. This paper discusses GIS and Remote Sensing tools application as a strategy to explore viable and economical prospective of floodwater management for spate irrigation. The fundamental problem is the optimal conservation of hill torrents flows and management of these water resources. To tackle this problem, a study for reservoir site selection was carried out. In this study, we present cost effective approach to mitigate the flood hazard while conserving this floodwater as irrigated water supply to minimize drought threats for a spate irrigation system. The novelty of study is development of a methodology for estimation of water holding capacity for reservoir by using geo-informatics tools. The objectives of paper are i. to demarcate the potential catchments of spate irrigation system and ii. floodwater storage by siting reservoir with geo-informatics tools. As an auxiliary output, a geo database is generated for intend to use its attribute data and spatial data for future research projects. This geo database include data layers of satellite imagery, GPS aided ground control points, irrigation network, catchments, administrative boundaries, proposed reservoir site location and digitized linear and polygon features. The results of this study depict that agricultural water management would be carried out efficiently with the use of developed methodology. The reliability of proposed reservoir solution is higher due to the use of high resolution datasets.